(untitled) (Research, Society and Development, 2021)
Duponchelia fovealis is an agricultural pest that causes great losses in strawberry plantations. As an alternative to traditional chemical insecticides, entomopathogenic fungi (EPF) are used to control this pest. One way to increase the effectiveness of these EPF is by combining them with plant extracts or essential oils (EOs). We carried out a literature review in the Web of Science database using Bibliometrix (version 4.0.0. – R free software tool). Our purpose was to analyze data on the use of EOs or plant extracts with microorganisms to control pests, and observe research trends on this topic. Between 1994 and 2020, 112 articles were published, with the Egyptian Journal of Biological Pest Control as the most outstanding journal. The country with the greatest number of publications on the topic in the analyzed period was Brazil (n=38), followed by India (n=26) and the United States (n=20). Keywords that stood out the most were compatibility, entomopathogenic fungi, Beauveria bassiana, biological control, Azadirachta indica, silver nanoparticles, entomopathogenic fungus, Metarhizium anisopliae, neem, and biocompatibility. Although this research field is growing, no record of a link between EPF and EOs or “plant extracts to control Duponchelia fovealis” was found.